FEATURES OF THE OSCILLATIONS OF ELECTRIC LOCOMOTIVES WITH TRACTION DRIVE CLASS II - Blokhin, E. P.; Korotenko, M. L.; Hranovskyi, R. B.; Chumak, V. V.; Harkavi, M. Ya.; Dzychkovskyi, E. M. (Science and Transport Progress, 2005)
The paper is dedicated the influence of the draft engine and reduction placement; it also concerns the oscillation of the the bogie frames and the locomotive body, which has a draft drive suspension of the 2nd class